An Analysis of Students Speaking Anxiety of Eleventh Grade Students at SMK Negeri 1 Lubuk Pakam - Aulia Ade Tiara; Asnawi Asnawi (Continuous Education: Journal of Science and Research, 2023)
The objective of the research is to know the causes of students' anxiety in speaking English, the types of students' anxiety, and the level of students' anxiety in speaking English in the eleventh grade of SMK Negeri 1 Lubuk Pakam. This study uses qualitative methods by collecting data through observation, interviews, questionnaires, and documentation. The results of this study indicate that there are 3 factors of student anxiety in learning English according to Horwits' theory (2011), namely (1) Communication Apprehension, where students have difficulty speaking English because they do not have much knowledge about English, (2) Test Anxiety, where students feel anxious when they have to take an English test, and (3) Fear of Negative Evaluation, where students are afraid that the teacher and their friends will laugh if students make mistakes. According to Thomas (2009), there are also two types of student anxiety: State Anxiety and Trait Anxiety. And the questionnaire was developed by Horwitz with 33 statements, the results showed that 1 student (10%) experienced a high level of anxiety, 7 students (70%) experienced a moderate level of anxiety, and 2 students (20%) experienced mild anxiety.